A Single-center Experience and Review of the Literature: 64 Cases of Phyllodes Tumors to Better Understand Risk Factors and Disease Management. Issue 3 (March 2015) - Lightner, Amy L.; Shurell, Elizabeth; Dawson, Nicole; Omidvar, Yasaman; Foster, Nova
Phyllodes tumors of the breast are rare fibroepithelial tumors that are characterized as benign, borderline, or malignant based on cellular characteristics such as stromal overgrowth and number of mitoses. Currently, there is a lack of consensus on risk factors and management of patients with phyllodes tumors, which has led to variation in treatment patterns as well as patient outcomes across many institutions. This study seeks to understand the clinicopathologic features, risk factors for local and metastatic recurrence, and clinical outcomes of patients with phyllodes tumors to better define optimal treatment patterns.